Macroeconomics Effects of Private Sector Participation in Latin America's Infrastructure - Trujillo, Lourdes; Martin, Noelia; Estache, Antonio; Campos, Javier (World Bank, Washington, DC, 2014)
The authors provide empirical evidence on the impact that private participation in infrastructure has had on key macroeconomic variables in a sample of 21 Latin American countries from 1985-98. Specifically, they look at the effects on GDP per capita, current public expenditures, public investment, and private investment, controlling for country effects and institutional factors. The authors also investigate the relevance of the specific contractual form of private participation contracts on these variables and show differentiated effects according to contract types. The results suggest that: 1) Private sector involvement in utilities and transport have some, but not impressive, positive effects on GDP per capita. 2) There is some degree of crowding-out of private investment resulting from greenfield projects in utilities, and delayed crowding-in from concessions in transport. 3) There is crowding-in of public investment by private participation in utilities, while there is crowding-out by increased private investment in transport. 4) Private participation in utilities decreases recurrent expenditures, while in transport it results in an increase. The net effect on the public sector account is uncertain, but this uncertainty is a major risk. The revelation of this risk may be the main contribution of this paper since it is inconsistent with the fiscal gains expected by many policymakers as they engage in infrastructure privatization programs.